Revista bilingüe para fomentar la participación intrínseca en la escritura creativa y la expresión artística de los estudiantes de la Licenciatura en Español e Inglés de la UAN (2024)
The project addresses the importance of university students' participation in extracurricular activities, highlighting that a lack of interest can lead to academic difficulties and a disconnect from the educational institution. It emphasizes the need to reflect on strategies to motivate participation, which directly influence academic performance and student engagement, pointing out factors such as family environment, self-esteem, and the quality of teaching.